First Report of Gametogenesis and Spawning for the Invasive Alga Caulerpa cylindracea in the Tyrrhenian Sea: The Key Role of Water Motion and Temperature - Caronni, Sarah; Delaria, Maria Anna; Gentili, Rodolfo; Montagnani, Chiara; Navone, Augusto; Panzalis, Pieraugusto; Citterio, Sandra (Frontiers in Marine Science, 2021)
In this paper gamete release by C. cylindracea was investigated for the first time in the Tyrrhenian Sea (Sardinia, Western Mediterranean), focusing on the main environmental factors triggering the species gametogenesis and spawning. To the purpose, a combined field and laboratory experiment was conducted. First, a two year mensurative experiment was performed in the field during summer to individuate and quantify the occurrence of C. cylindracea gametogenesis and spawning events, linking them to the environmental conditions. Then, based on the results of the field work, a laboratory experiment was performed to directly test, in controlled conditions, the effect on the above mentioned processes of the two abiotic factors that appeared to play a key role in the species gamete release processes in the area: sea water temperature and water movement. During the two-year period of field research, several gametogenesis events were recorded in the study area and two spawning events also occurred. Moreover, significant differences in the ratio between fertile and total thalli, as well as that between releasing and fertile ones were observed among sites characterized by a different water movement and among sampling periods with different sea water temperatures. Overall, these results suggest that C. cylindracea sexual reproduction occurs also in the Tyrrhenian Sea and that, therefore, new more invasive genotypes of the species could be produced in the basin, where both its gametogenesis and spawning seem to be mainly regulated by water movement and sea water temperature.